2012
DOI: 10.5664/jcsm.2256
|View full text |Cite
|
Sign up to set email alerts
|

Association between QRS Duration and Obstructive Sleep Apnea

Abstract: QRS duration and OSA were significantly associated. Severity of OSA independently predicted prolonged QRS in women but not men. Nevertheless, prolongation of QRS duration in either sex may potentiate arrhythmic risks associated with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
2
15
1
Order By: Relevance
“…[ 25 ] Desai et al reported that QRS duration was a significant and independent predictor of cardiovascular mortality in general medical population. [ 26 ] Similar to the previous one,[ 27 ] our study also found that OSAS patients had prolonged QRS duration. Another point to be considered was the higher numbers of male patients in the OSA group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[ 25 ] Desai et al reported that QRS duration was a significant and independent predictor of cardiovascular mortality in general medical population. [ 26 ] Similar to the previous one,[ 27 ] our study also found that OSAS patients had prolonged QRS duration. Another point to be considered was the higher numbers of male patients in the OSA group.…”
Section: Discussionsupporting
confidence: 89%
“…While OSA patients revealed longer QT durations similar to our study in literature,[ 29 ] in the study of Gupta et al mentioned above, there was no significant lengthening in QRS duration. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association between SDB and QRS duration is in line with the finding of Gupta et al in which severity of sleep apnea was associated with prolonged QRS in women, but not in men [33]. Since prolonged QTc is a well-known ECG marker for cardiovascular risk including sudden cardiac death [34, 35], an association of SDB with QTc prolongation might be a mechanism underlying the reported associations of SDB with adverse cardiovascular outcome and sudden cardiac death [36, 37].…”
Section: Discussionsupporting
confidence: 87%
“…QRS duration) is a significant clinical marker in terms of the ventricular arrhythmic risk in OSA patients. [ 21 ] In fact, data from our study might support a potential autonomic mechanism given that PAF patients (of whom 82% were on beta-blockers) were less susceptible to simulated OSA manoeuvres in Pd and P-wave duration. In addition, augmented oxidative stress has been suggested to increase the risk of cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 68%